Implementasi Platform Si Cantik Bangsa di Kabupaten Kebumen dalam Pembangunan Desa - Arief Rais Bahtiar; Rima Dias Ramadhani; Alfin Hikmaturokhman; Novanda Alim Setya Nugraha; Pradana Ananda Raharja; Novri Anto; Bunga Laelatul Muna; Rehan Nur Setiawan; Moh Lutfi Fadilah; Satya Helfi Agustianto; Yasinta Swasti Mahargyani; Adhi Purwono (Warta LPM, 2024)
Si Cantik Bangsa is a platform that aims to record participation and equality in village development. Through this community service, the focus is emphasized on understanding the problems of women's empowerment in development in three villages, namely Logede Village, Ampelsari Village, and Kaliputih Village in Kebumen Regency. In this context, the main concern is overcoming the significant decline in the Gender Empowerment Index which is a serious challenge faced by the Community and Village Empowerment Service (PMD). In an effort to overcome this problem, the PMD Department introduced an innovative program known as Planning Literacy Women (WANI LEmPER) which is in line with the Sustainable Development goals (SDGs) related to gender equality and women's empowerment. However, even though the WANI LEmPER program has been implemented, there are still obstacles that arise due to cultural resistance and rejection from various parties. Therefore, this service offers a solution through the implementation of Si Cantik Bangsa, an information technology-based platform that aims to document the activities of LEmPER WANI cadres and monitor women's participation. The service results show that indicators of success have been achieved, where 65% of respondents understand the benefits and features of Si Cantik Bangsa, while 25% still do not understand them. Thus, the use of this platform is considered a strategic step in increasing women's empowerment in village development planning to achieve SDGs and Gender Empowerment goals.